The Role of Social Norm in Acceptability Attitude of Women Toward Intimate Partner Violence in Punjab, Pakistan - Nadeem, Muhammad (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) is a public health and human rights issue with the social and economic impacts felt by women. Punjab is a male-dominated society, where partner violence is generally accepted as a cultural norm and viewed as normal behavior within a marriage. It stems from attitudes that partner violence is a private matter and usually a justifiable response to misbehavior on the part of the wife. The focus of the current study is to investigate the impact of this cultural norm in acceptability attitude of women toward IPV in Punjab province. A large-scale sample size of more than 46,000 from Multi-Indicator Cluster Survey (MICS) 2018 has been used. The impact of the cultural norm on the wife-beating attitude has been investigated in five dimensions: wife going out without telling him, neglecting the children, arguing with him, refusing to have sex with him, and burning the food. The logistic regression results indicate that wife-beating is accepted as a community norm. It has been found that if wife-beating is accepted by community, then the individual female is more than 3 times more likely to consider it justifiable in all five dimensions. The other important factors are education level, household wealth, ethnicity, media exposure, and wife–husband age difference. The level of education of women plays the most important role in rejecting the wife-beating norm, as an increase in level of education is associated with an increase in the probability of rejecting the wife-beating. So, the current study suggests that there is a dire need to increase the female education level to overcome this issue.